2011
DOI: 10.1007/s12020-011-9438-5
|View full text |Cite|
|
Sign up to set email alerts
|

Preimplantation factor (PIF) analog prevents type I diabetes mellitus (TIDM) development by preserving pancreatic function in NOD mice

Abstract: Preimplantation factor (PIF) is a novel embryo-secreted immunomodulatory peptide. Its synthetic analog (sPIF) modulates maternal immunity without suppression. There is an urgent need to develop agents that could prevent the development of type 1 diabetes mellitus (TIDM). Herein, we examine sPIF's preventive effect on TIDM development by using acute adoptive-transfer (ATDM) and spontaneously developing (SDM) in non-obese diabetic (NOD) murine models. Diabetes was evaluated by urinary and plasma glucose, intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 41 publications
7
58
0
Order By: Relevance
“…Importantly, we reported that in human immune cells PIF targets both thrombin and S100-A8, thus through local action PIF could mitigate such pathology [33]. PIF reduced systemic NK cells cytotoxicity and up-regulated local HLA-C expression, suggesting an integrated protective action [37]. PIF and P4 only mildly affected HLA-F expression, confirming previous observations [14].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Importantly, we reported that in human immune cells PIF targets both thrombin and S100-A8, thus through local action PIF could mitigate such pathology [33]. PIF reduced systemic NK cells cytotoxicity and up-regulated local HLA-C expression, suggesting an integrated protective action [37]. PIF and P4 only mildly affected HLA-F expression, confirming previous observations [14].…”
Section: Discussionsupporting
confidence: 80%
“…These are prime PIF targets which are also regulated in vivo [26, 33, 37]. Mitogenic effects of EGF were reduced by lowering its receptor levels, which is likely to support trophoblastic differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of fulminant type 1 diabetes remains unclear [13]. Some evidences suggest that both genetic factors, such as human leukocyte antigen (HLA) [10], and environmental factors, such as viral infection, contribute to the development of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that PIF is present in maternal circulation, and is expressed by the human placenta and fetus [4,5,[13][14][15]. Relevant to PIF's immune regulatory features, translational aspects to treatment of non-pregnant autoimmune and transplantation models were documented [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%